2014
DOI: 10.3986/ags54108
|View full text |Cite
|
Sign up to set email alerts
|

The importance of vulnerable areas with potential tourism development: a case study of the Bohemian forest and South Bohemia tourism regions

Abstract: The significance of the vulnerability of nature-rich areas with high development potential for tourism was studied using three types of data: 1) spatial distribution of tourist attractions, 2) the appeal level of these attractions, and 3) the number of visitors. The Bohemian Forest and South Bohemia were chosen as study areas. Nine types of landscape spatial appeal were identified in the study area. Two most important types were defined based on their appeal where there are rare relic features in the natural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Most of the area is a part of the Protected Landscape Area named Třeboňsko (Navrátil et al. ) established in 1979 with an area of 700 km 2 . Before this, Třeboňsko had been declared as a Biosphere Reserve in the UNESCO Man and the Biosphere Programme in 1977.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the area is a part of the Protected Landscape Area named Třeboňsko (Navrátil et al. ) established in 1979 with an area of 700 km 2 . Before this, Třeboňsko had been declared as a Biosphere Reserve in the UNESCO Man and the Biosphere Programme in 1977.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the process of forward selection was repeated. The model was assessed based on partial regression graphs and partial residual graphs, and the method was assessed by means of the F-test of importance of a regression model and Adjusted R 2 (Meloun and Militký [62], Navrátil et al [63]). …”
Section: Links Between the Location Of Agricultural Ad Plants And Natmentioning
confidence: 99%
“…Nevertheless, other areas are also in a similar situation (Havrlant, 2001;Havrlant, 2010;Foret and Klusacek, 2011). It has been shown that large-area protected territories represent a major concentration of accommodation facilities in the observed area and environment of the protected areas are the threatened ones, as intensively studied by Navrátil et al (2013Navrátil et al ( , 2014.…”
Section: Methodsmentioning
confidence: 91%